PENGARUH PENDEKATAN BISIK BERANTAI TERHADAP KETERAMPILAN BERBICARA SISWA SPEECH DELAY - Nurwahida, Nurwahida; Rukli, Rukli (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
This study aims to test the effectiveness of the chain whisper approach in improving children's speaking skills with Speech Delay at UPT SDN 15 Sela, Bungoro District, Pangkajene and Islands Regency. This research uses the single subject research (SSR) method with an ABAB design. The research subject is an 11 year old boy who is currently in grade 5 of elementary school with Speech Delay named Safaruddin. The research results show that the chain whisper approach is effective in improving the speaking skills of children with speech delay. In the baseline phase, research subjects were only able to speak 40%. In the intervention phase, research subjects were 60% able to speak. In the advanced baseline phase, research subjects were 73% able to speak. In the advanced intervention phase, research subjects were 91% able to speak. Based on the results of this research, it can be concluded that the chain whisper approach is an effective intervention to improve the speaking skills of children with speech delay